Delay probability in adaptive systems based on activation function of classical neural networks - Maja Lutovac Banduka; Vladimir Mladenović; Danijela Milosević; Vladimir Orlić; Asutosh Kar (Egyptian Informatics Journal)
Many improved algorithms have been proposed for nonlinear system designs. There is no single procedure for providing an algorithm with closed-form system response relations as a function of system parameters. In this paper, we illustrate a unique method for discrete-time digital nonlinear systems. Provides better insight into the analyzed system, algorithm, and processes. The main contribution is closed-form symbolic responses in the time domain and modifications of the implemented algorithm. A comparison of adaptive systems and neural networks is also presented. The design and analysis of nonlinear systems are more clearly simplified for either engineers or researchers without deep mathematical knowledge.